Hubungan Masa Kerja Terhadap Kemampuan Kepemimpinan Guru dalam Membangun Kolaborasi dengan Rekan Sejawat - Ahmad Junaidi; Dwi Supriatin; Ni Putu Novie Yanti. A.; Moh.Noor Supandri; Lalu Abi Said Ali; Saefulloh; A Wahab Jufri (Postgraduate University of Mataram, 2025)
This study aims to investigate the relationship between teachers' tenure and their leadership skills in building collaborative relationships with colleagues in the school environment. Collaboration among teachers plays an important role in building a positive work culture and supporting professional development at both the individual and organizational levels. Tenure is often considered an influential indicator of leadership style, and teachers with more experience tend to demonstrate a deeper understanding of the challenges and strategies required to build effective working relationships. This study used a quantitative method with a descriptive approach. Data collection was carried out using a questionnaire targeting 163 respondents in the West Nusa Tenggara region with the results of 61.3% of teachers having a tenure of more than 10 years. While the ability of teachers in building collaboration respondents answered consistently as much as 58% so that the leadership ability of teachers in building collaboration with colleagues can be said to be good. The results of this study support that teacher tenure contributes significantly to the development of leadership skills. Experienced teachers are better able to build working relationships based on mutual trust and effective collaboration. The results of this study are expected to provide insights to policy makers regarding the design of training programs that focus not only on developing teaching skills but also leadership skills. This research can also be a reference for future research to deepen the dynamics of teacher leadership in the educational environment.